Development An Ontology-based Approach for Risk Analysis and Assessment in Construction - الدبس هبة; فايز جراد; لما سعود (Latakia University Journal -Engineering Sciences Series, 2023)
Construction projects face a high level of risks and uncertainties, due to external and internal conditions and variations. Risks possibly cause delay, cost overrun, and even poor quality. Effective risk management is hence necessary to mitigate the impact of potential risks, and ultimately ensure project success. This area of research needs more research and development. With the increasing importance of knowledge , and the introduce of the prior knowledge in the identification and assessment risk process. Several approaches have been proposed such as ontology that follows a risk path approach. This study aims to develop an ontology as a knowledge-based system of the risk management of construction projects. Ontology organizes risk knowledge into six unified classes ( process, parties, product, resource, contract, and External environment). Defined classes, together with corresponding properties and relations, are coded using the Protégé program. Ontology is evaluated theoretically and practically by using five case studies. The developed ontology could be used to support decision-making during risk management. The developed ontology may facilitate building a corporate memory system, developing databases, and developing a model to support the systematic risk assessment and analysis.